MODERNISASI DAN WESTERNISASI: STUDI TERHADAP PERUBAHAN KEBIASAAN PENGONSUMSIAN TEH DALAM MASYARAKAT JEPANG - , LAILY AMALIA SAVITRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper explains about the changing habits of tea consumption in Japanese society from Azuchi-Momoyama period to Heisei period. The first habit of tea consumption was chanoyu, but, along with the modernization in Japan, that habit was changed and evolved into more modern habits of tea consumption.The aims of this studyare to know the development, the influence of modernization, and the classification of the kinds of cultural changes in the habits of tea consumption. The data collection method was a library research. To analyze the data used the identification of comparison method. Data from these comparisons used to analyze the influence of modernization and to classify the kinds of cultural changes in the habits of tea consumption with the concepts of cultural changes and modernization. The conclusions of this study are the changing habits of tea consumption can be occur either before, while, and after modernization. The influence of modernization in the habits of tea consumption occurred in sector social and economic. The kinds of cultural changes in the habits of tea consumption mostly arein the category of innovation and acculturation. From this study is also known that the modernization in the habits of tea consumption is not the same as Westernization because it doesnât make the Japanese society to be \"less Japanese\".